Soulshaping a journey of self-creation - Brown, Jeff 1962- (Berkeley, California North Atlantic Books, 2009)
"The story of a brilliant young trial lawyer who struggled to find his true path, this engaging, inspirational memoir takes readers through profoundly human terrain--unresolved emotional issues, economic obstacles, confusion, self-doubt, and what the author calls "the school of heart knocks"--on a soul-searching journey toward heart-consciousness and spiritual authenticity" --Provided by publisher.
Includes bibliographical references.
Donated by Atty. Mehol K. Sadain, UP Institute of Islamic Studies, 2018.
Keywords: Self-actualization (Psychology) -- Case studies; Spiritual life -- Case studies; Mind and body therapies -- Case studies; Spiritual biography; Lawyers -- Ontario -- Biography